1838. Digging Deeper: A Closer Look at Core Elements of Antibiotic Stewardship for Long-Term Care Facilities. (26th November 2018) - Lodhi, Hanan Tahir; Bergman, Scott; Chung, Philip; Rupp, Mark E; Vanschooneveld, Trevor; Ashraf, Muhammad Salman
Abstract: Background: The CDC encourages all long-term care facilities (LTCF) to develop antibiotic stewardship programs (ASP) consisting of seven core elements (CE). These CE include leadership commitment, accountability, drug expertise, action, tracking, reporting and education. However, action include three essential sub-elements (SE): policy development, practice implementation and pharmacist involvement. Similarly, tracking has two major SE; antibiotic use and outcome measures. Typically, a multi-component CE is considered met if any of the SE is present. We evaluated application of a strict definition that requires all major SE to be present for the action and tracking CE to be considered met. Methods: A group of consultant pharmacists (CP) was trained to evaluate and lead ASP in their LTCF. Baseline ASP evaluation was conducted by CP in 29 LTCF using the CDC CE checklist between November 2017 and January 2018. CE credits were assigned to LTCF ASP using conventional (any SE) and strict definitions (all SE required). Results were compared among LTCF ASP using both definitions. Results: None of the LTCF has all seven CE regardless of the definition. A median of two CE (range 1–6) were present based on conventional definition (CD) and 1 (range 0–5) using the strict definition (SD). Less than a quarter of LTCF ( n = 6, 20.6%) met five or more CE with the CD and only one (3.5%) using the SD. Interestingly, when utilizing the CD, all (100%) LTCF met at least one CE as compared with only 16 (55.1%) when using the SD. The action CE is most frequently met when using CD and least frequently met when using SD (Figure 1). CP reviewing a proportion of antibiotic orders as a part of their monthly drug regimen review was the most common action and was met by 89.7% of LTCF. Only 2 (6.9%) LTCF had stewardship policies and 4 (13.8%) had implemented at least one stewardship practice. Similarly, 20 (69.0%) LTCF had tracking based on the CD with a majority (55.2%) tracking outcome measures and some (41.4%) tracking antibiotic use. However, only a quarter (27.6%) of LTCF were tracking both outcomes and antibiotic use. Conclusion: Many LTCF have some components of action and tracking CE in place but are missing important SE. Data on CE should be collected in a manner that makes it easier to identify these deficiencies during LTCF ASP evaluation. Disclosures: T. Vanschooneveld, Merck: Grant Investigator, Grant recipient. M. S. Ashraf, Merck & Co. Inc.: Grant Investigator, Research grant.